# Social Studies

After identifying the problem, which of the following is the next step an engineer usually takes
A. Explore what other people have done about the problem
B. Build a prototype to solve the problem
C. Identify related problems
D. Communicate the results of prototype testing

1. 👍
2. 👎
3. 👁

1. 👍
2. 👎
👤
Ms. Sue
2. The usual next step, is A. Those who like to their heads against brick walls, do B.
those who do not take their meds regularily, often start with C, and those who want to run for president do D.

1. 👍
2. 👎
👤
bobpursley
3. LOL!

1. 👍
2. 👎
👤
Ms. Sue
4. wow puresly ur funny

1. 👍
2. 👎

## Similar Questions

1. ### LA

What is the final step in evaluating the information in a video? a. listing key details b. summarizing ideas c. identifying the subject d. recording central ideas

2. ### Physics

An engineer in a locomotive sees a car stuck on the track at a railroad crossing in front of the train. When the engineer first sees the car, the locomotive is 210 m from the crossing and its speed is 26 m/s. If the engineer’s

3. ### Math - HELP FAST

In deciding the best medium to tell a story, which step is first?(1 point) deciding how much to leave to the imagination thinking about what the characters are doing identifying the audience figuring out the setting

4. ### math

Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

1. ### physics

if it takes 726 watts of power to move a mass 36 meters in 14 seeconds, what is the mass? i really need like, step by step help please? asap. thanks, michelle .

2. ### Algebra

Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below. Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x = 7−6 Step 4: x = 1 In which step did Josephine make an error? A- step 4 B- step 1 C- step 2 D-

3. ### math

Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

4. ### ALGEBRA HELP

When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

1. ### algebra

write a function rule for the table. y= x -10, -7, -2, 6, 10 y -25, -19, -9, 7, 15 Can someone please show me step by step how to work this problem out step by step, I am so confused.

2. ### chemistry

This question I really don't get it. I tried tried tried to figure out how to start solve the problem but still couldn't figure out. So can you help me with one question PLEASE? If so, can you please explain to me how you get the

3. ### college physics

A 55 kg engineer leaves her office on the 33rd floor of a skyscraper and takes an elevator to the 59th floor. Later she descends to street level. If the engineer takes her office as the zero for potential energy and if the

4. ### Math

I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 −